Performance modulation of transparent ALD indium oxide films on flexible substrates: transition between metal-like conductor and high performance semiconductor states. Issue 32 (25th July 2016) - Sheng, Jiazhen; Choi, Dong-won; Lee, Seung-Hwan; Park, Jozeph; Park, Jin-Seong
Abstract : Atomic layer deposited indium oxide films with the hydrogen peroxide reactant exhibited performance modulation between a semiconductor and a conductor on a flexible substrate. Abstract : Indium oxide (InO x ) films are grown by atomic layer deposition (ALD) using [1, 1, 1-trimethyl- N -(trimethylsilyl)silanaminato]-indium (InCA-1) as the metal precursor and hydrogen peroxide (H2 O2 ) as the oxidant. It is found that the electrical properties of the indium oxide layers strongly depend on the ALD growth temperature. Relatively low electrical resistivity (∼10 −4 Ω cm) and high optical transparency (>85%) are obtained at growth temperatures higher than 200 °C, which make the indium oxide film suitable for transparent conducting oxide (TCO) applications. On the other hand, at relatively low growth temperatures below 150 °C, indium oxide behaves as a transparent semiconducting oxide (TSO). Thin film transistors (TFTs) incorporating this material as the active layer exhibit reasonably high performance with saturation mobility exceeding 10 cm 2 V −1 s −1 and a threshold voltage near 0 V.